Is English language as a medium of instruction a hurdle for first year MBBS teaching learning? Perceptions of students and teachers - Gupta, Madhur M.; Deshmukh, Mahesh; Chari, Suresh (International Journal of Research in Medical Sciences, 2017)
Background: Presently there is a linguistic dualism i.e. thinking in one language and studying in the other. Proficiency in English is the need of the hour. However, for some an abrupt change in the medium of language along with introduction of terminologies can become a potential barrier to academic success. Methods: A questionnaire based study was carried out in 150 students and 25 teachers of first MBBS. Results: Majority of the students and teachers considered that English as a medium of instruction is not a problem. They also opined that English should be retained as a medium of instruction since it is of global importance; use of regional /national language should be allowed since it will help in dealing with patients and thus better patient care. Conclusions: Since English is the language of global importance, medical teachers should work together to find out a practical approach in addressing some of the problem areas faced by few medical students to help them perform better as an Indian medical graduate.